FLOUTING MAXIM IN CREATING VERBAL HUMOR IN THE PRETTY SMART NETFLIX SERIES - Hakim, Muhamad Syahril Adil; Indah, Rohmani Nur (Annual International Conferences on Language, Literature, and Media, 2022)
Humor is a complex social phenomenon generally encountered around us. It is repeatedly used in mass entertainment. However, humor is still a relatively uncommon topic in research. Therefore, this study attempts to uncover verbal humor in Pretty Smart Netflix Series. The two objectives of this study are to identify the types of flouting maxims and describe the flouting maxim employed by the characters to produce verbal humor. This research used a descriptive qualitative method by employing Grice’s Cooperative Principle theory and Shade’s verbal humor theory. Twenty floating maxims were included in the seven episodes of the Pretty Smart Series. The most frequent type found is the flouting maxim of quality, followed by the flouting maxim relation and the flouting maxim of quantity, and the last is the flouting maxim of manner. These flouting maxims create types of verbal humor, including jokes, irony, wit, and satire. This research can be used as a reference for further research to understand Pragmatics, particularly regarding the flouting maxims and verbal humor.